KRITIK TERHADAP PANDANGAN VERIDIKALISME MENURUT PANDANGAN ALKITAB - Yusak Noven Susanto (Alucio Dei, 2021)
Veridicalism is an understanding that is based on a trustworthy truth if it can be verified. Because according to this view, belief must be built from proven evidence. If it cannot be proven and cannot be verified, it can be doubted and abandoned because there is no truth in it. This is acceptable but on the other hand this view is unacceptable. Like the story found in the Word of God, when the Lord Jesus Christ made miracles which of course scientifically cannot be proven. But when you see this is it not true or not? Of course it is true and happened. Therefore, in this study the researcher wants to criticize this Veridicalism view based on the Biblical viewpoint. The method that researchers use in this research is the literature research method, which uses sources that support the description of Veridicalism and the Bible. The purpose of this research is to show believers God's intention and provide an explanation of the viewpoint of Veridicalism which cannot fully become the basis of life for believers today.